Pentingnya Manajemen Sekolah dalam Peningkatan Mutu Pendidikan di Sekolah Dasar - Utomo (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
School management can be interpreted as everything related to the management of the educational process in order to achieve the goals that have been set, both short, medium, and long-term goals. The purpose of this study is to determine school management in improving the quality of education, including: (1) School program planning; (2) Implementation of school programs and (3) Obstacles they face. This research uses a qualitative approach with a descriptive method, data collection techniques are carried out through interview guidelines, observation guidelines, and documentation studies. The subject of the study was the principal of Bojonggaling Elementary School. The results of his research found: (1) School program planning includes: teaching programs, including: the needs of teachers for the distribution of teaching tasks, procurement of textbooks, teaching aids and teaching aids, procurement or development of school laboratories, procurement or development of school libraries, learning outcomes assessment systems, and curricular activities; (2) The implementation of school programs, namely strategies implemented to achieve improvement in the quality of education, including: program socialization, SWOT analysis, problem solving, quality improvement, and monitoring and evaluation of school program implementation; and (3) Barriers to school program planning, including lack of community participation and economic hardship, resulting in low support for school management. It is hoped that the supervisor will be able to direct and supervise the principal in improving the quality of education about school program planning, program implementation and the obstacles he faces in an appropriate, effective and efficient manner so that the quality of education in the school can be improved.